2021
DOI: 10.5334/gh.863
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Phenotypes and Subclinical Atherosclerosis in Adults from Sub–Saharan Africa: An H3Africa AWI–Gen Study

Abstract: Background: Obesity and adipose tissue distribution contribute to an increased risk of cardiovascular disease (CVD) by promoting atherosclerosis. This association has been poorly studied in sub–Saharan Africa (SSA) despite the rising prevalence of cardiovascular disease. Objectives: We determined the association between various adiposity phenotypes and carotid intima–media thickness (CIMT), a proxy of subclinical atherosclerosis, in a large SSA population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For example, a recent study reported that fine-scale population structure was strong enough to influence association signals among the South African participants from our cohort 51 . This, added to environmental and lifestyle differences within and between geographic regions, as observed in several phenotype studies based on the AWI-Gen cohort 34 , 35 , 52 , 53 , could limit the ability of modest sample size GWAS based on pan-African datasets to identify associations accurately. We have employed a LMM based approach to conduct association testing on the full dataset with principal components as covariates for the Stage 1 GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study reported that fine-scale population structure was strong enough to influence association signals among the South African participants from our cohort 51 . This, added to environmental and lifestyle differences within and between geographic regions, as observed in several phenotype studies based on the AWI-Gen cohort 34 , 35 , 52 , 53 , could limit the ability of modest sample size GWAS based on pan-African datasets to identify associations accurately. We have employed a LMM based approach to conduct association testing on the full dataset with principal components as covariates for the Stage 1 GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…The mean-max cIMT was generated as the average of the maximum cIMT from the left and right carotid arteries, and this value was used for the GWAS analyses. The association of cIMT with non-genetic risk factors in our cohort have been documented 26,61 .…”
Section: Methodsmentioning
confidence: 67%
“…The Africa Wits-INDEPTH Partnership for Genomic Studies cohort (AWI-Gen) was developed to examine genetic and environmental contributions to cardiometabolic diseases in Africans. It has over 12,000 participants from four sub-Saharan African countries, Burkina Faso, Ghana, Kenya and South Africa, and the distributions and associated risk factors for cIMT have been described [23][24][25][26] . This study aimed to investigate genetic susceptibility to atherosclerosis in sub-Saharan Africans in the AWI-Gen cohort.…”
mentioning
confidence: 99%